Epigenetically regulated miR-1247 functions as a novel tumour suppressor via MYCBP2 in methylator colon cancers. Issue 10 (13th November 2018) - Liang, Jennifer; Zhou, Wenchao; Sakre, Nneha; DeVecchio, Jennifer; Ferrandon, Sylvain; Ting, Angela; Bao, Shideng; Bissett, Ian; Church, James; Kalady, Matthew
Abstract Background Colorectal cancer (CRC) is a heterogeneous disease with distinct clinical subsets based on underlying genetic and epigenetic changes. DNA hypermethylation yields a unique CRC subset with a distinct phenotype and clinical behaviour, but this oncogenic pathway is not fully characterised. This study identifies and characterises miR-1247 as a novel tumour suppressor microRNA in methylated human colon cancers. Method Tumour samples from patients with hypermethylated and non-methylated colon cancer and cell lines were evaluated for miR-1247 expression and function. A murine subcutaneous xenograft model was used for in vivo functional studies. Results miR-1247 was methylated and underexpressed in methylator colon cancers. Overexpression of miR-1247 significantly inhibited cell proliferation, decreased tumour cell motility, induced apoptosis, and mitigated tumour formation capacity both in vivo and in vitro. Pharmacologic demethylation increased miR-1247 expression and produced similar anti-tumour activities. Mechanistic investigations revealed that MYCBP2, a member of the c-myc oncogene family, is a direct functional target of miR-1247. Furthermore, in CRC patients, MYCBP2 protein levels are associated with miR-1247 levels and survival. Conclusions miR-1247 acts as a tumour suppressor by inhibiting MYCBP2 in methylator colon cancer. The MYCBP2/c-myc axis may underlie the anti-tumour activities of miR-1247 and is a potential therapeutic target via demethylation agents.